The Use of an Information System to Manage Vocational Assessment in Facing the 5.0 Digital Society - I Made Sudana; Syaad Patmanthara; Dhega Febiharsa; Benti Gandisa (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
Social distancing policy is applied during the Covid-19 virus pandemic including in Batik Professional Certification Institution in Indonesia. The management should provide services for the participants without meeting them directly. This study aims to reveal the management of Batik competence tests during the Covid-19 virus pandemic. The observation focused on the performance of the administrative staff, assessors, and management staff of the Batik Professional Certification Institutions (PCI). This is a qualitative study. The data were collected through questionnaires distributed to the participants, assessors, and administrators. The research concerns on the role and impact of the use of information system management in the interaction between prospective assessment, participants, assessors, and management of PCI in the professional certification competency test (PCCT). The findings showed that the use of information systems to manage vocational assessment has been effective to inform the assessment schedule to the assessor and participant, bridging the assessment reports, and reminding license expiration to management, so the management has an efficient way to manage the information with this system automation.